Constructing Built-In Electric Fields with Semiconductor Junctions and Schottky Junctions Based on Mo–MXene/Mo–Metal Sulfides for Electromagnetic Response - Zeng, Xiaojun; Jiang, Xiao; Ning, Ya; Gao, Yanfeng; Che, Renchao (Nano-micro letters, 2024)
Highlights Mo–MXene/Mo–metal sulfides with semiconductor junctions and Mott–Schottky junctions are designed. Built-in electric field are constructed in semiconductor–semiconductor–metal heterostructure, enhancing dielectric polarization and impedance matching. Density functional theory calculations and Radar cross-section simulations confirmed the excellent electromagnetic wave absorption ability of heterostructures. The exploration of novel multivariate heterostructures has emerged as a pivotal strategy for developing high-performance electromagnetic wave (EMW) absorption materials. However, the loss mechanism in traditional heterostructures is relatively simple, guided by empirical observations, and is not monotonous. In this work, we presented a novel semiconductor–semiconductor–metal heterostructure system, Mo–MXene/Mo–metal sulfides (metal = Sn, Fe, Mn, Co, Ni, Zn, and Cu), including semiconductor junctions and Mott–Schottky junctions. By skillfully combining these distinct functional components (Mo–MXene, MoS 2 , metal sulfides), we can engineer a multiple heterogeneous interface with superior absorption capabilities, broad effective absorption bandwidths, and ultrathin matching thickness. The successful establishment of semiconductor–semiconductor–metal heterostructures gives rise to a built-in electric field that intensifies electron transfer, as confirmed by density functional theory, which collaborates with multiple dielectric polarization mechanisms to substantially amplify EMW absorption. We detailed a successful synthesis of a series of Mo–MXene/Mo–metal sulfides featuring both semiconductor–semiconductor and semiconductor–metal interfaces. The achievements were most pronounced in Mo–MXene/Mo–Sn sulfide, which achieved remarkable reflection loss values of − 70.6 dB at a matching thickness of only 1.885 mm. Radar cross-section calculations indicate that these MXene/Mo–metal sulfides have tremendous potential in practical military stealth technology. This work marks a departure from conventional component design limitations and presents a novel pathway for the creation of advanced MXene-based composites with potent EMW absorption capabilities.